Recent developments, applications and challenges for carbon quantum dots as a photosynthesis enhancer in agriculture - Chowmasundaram, Yamuna; Tan, Tong Ling; Nulit, Rosimah; Jusoh, Mashitah; Abdul Rashid, Suraya (Royal Society of Chemistry, 2023)
Since the world's population is expanding, mankind may be faced with a huge dilemma in the future, which is food scarcity. The situation can be mitigated by employing sustainable cutting-edge agricultural methods to maintain the food supply chain. In recent years, carbon quantum dots (CQD), a member of the well-known carbon-based nanomaterials family, have given rise to a new generation of technologies that have the potential to revolutionise horticulture and agriculture research. CQD has drawn much attention from the research community in agriculture owing to their remarkable properties such as good photoluminescence behaviour, high biocompatibility, photo-induced electron transfer, low cost, and low toxicity. These unique properties have led CQD to become a promising material to increase plant growth and yield in the agriculture field. This review paper highlights the recent advances of CQD application in plant growth and photosynthesis rate at different concentrations, with a focus on CQD uptake and translocation, as well as electron transfer mechanism. The toxicity and biocompatibility studies of CQD, as well as industrial scale applications of CQD for agriculture are discussed. Finally, the current challenges of the present and future perspectives in this agriculture research are presented.